Answer:
(x + 2)² + (y + 9)² = 49
Step-by-step explanation:
Equation:
(x - h)² + (y - k)² = r²
(x - -2)² + (y - -9)² = 7²
(x + 2)² + (y + 9)² = 49
Answer:
a=567 km+900 km
a=1,467 km
b=567 km+169 km
b=736 km
x^2/a^2+y^2/b^2=1
x^2/(1,467)^2+y^2/(736)^2=1
Step-by-step explanation:
Answer:
D
Step-by-step explanation:
((p^4*q)/p^8)^2.
p^4/p^8=p^(4-8)=p^-4=1/p^4
(q/p^4)^2=(q^2/p^8)
Answer:
x=-10
Step-by-step explanation:
3x-4(2+3x)=82
3x-(4*2)+(4*3x)=82
3x-8-12x=82
-9x-8=82
-9x-8+8=82+8
-9x=90
-9x/-9=x
90/-9=-10
x=-10